Role of the Radiotherapy Boost on Local Control in Ductal Carcinoma In Situ. (8th April 2012) - Riou, Olivier; Lemanski, Claire; Guillaumon, Vanessa; Lauche, Olivier; Fenoglietto, Pascal; Dubois, Jean-Bernard; Azria, David
Abstract : Ductal carcinoma in situ of the breast is associated with low mortality rates, but local relapse is a matter of concern in this disease. Risk factors for local relapse include young age, close or positive margins, and tumor necrosis. Whole breast irradiation following breast-conserving surgery for ductal carcinoma in situ significantly reduces the risk of local relapse as compared to breast-conserving surgery alone. Studies point to similar outcomes between breast-conserving surgery plus radiotherapy and mastectomy, in the absence of extensive disease. A complementary boost to the surgical bed improves outcomes for patients with invasive breast cancer. However, the effect of this strategy has never been prospectively reported for ductal carcinoma in situ . Two randomized controlled trials assessing this issue are ongoing. This paper represents an update on available literature about radiotherapy for DCIS with a special focus on the role of a radiotherapy boost to the tumor bed.